2022
DOI: 10.1016/j.neubiorev.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Filling the gaps: Cognitive control as a critical lens for understanding mechanisms of value-based decision-making

Abstract: While often seeming to investigate rather different problems, research into value-based decision making and cognitive control have historically offered parallel insights into how people select thoughts and actions. While the former studies how people weigh costs and benefits to make a decision, the latter studies how they adjust information processing to achieve their goals.Recent work has highlighted ways in which decision-making research can inform our understanding of cognitive control. Here, we provide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 280 publications
(357 reference statements)
5
36
0
Order By: Relevance
“…The ability to weigh expected rewards and costs is critical for optimal decision-making (Frömer & Shenhav, 2021;Lopez-Gamundi et al, 2021;Westbrook et al, 2020). For instance, many everyday activities such as exercising (Harris & Bray, 2021) and helping others (Lockwood et al, 2017) involve physical effort.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to weigh expected rewards and costs is critical for optimal decision-making (Frömer & Shenhav, 2021;Lopez-Gamundi et al, 2021;Westbrook et al, 2020). For instance, many everyday activities such as exercising (Harris & Bray, 2021) and helping others (Lockwood et al, 2017) involve physical effort.…”
Section: Introductionmentioning
confidence: 99%
“…This renders moot any neural predictions that would theoretically follow from such an adaptive control account, and may explain why Vassena and colleagues were unable to find evidence that bore out these neural predictions. It remains to be determined whether previous adaptive control accounts can quantitatively account for patterns of dACC activity observed in this study, but at a qualitative level those patterns can be accounted for by any theory that implicates the dACC in monitoring for potential conflict (low value differences) and surprise (high value differences), including EVC 1,8,19,37,38 . Substantial progress has been made toward uncovering the neural and computational mechanisms at the intersection of value-based decision-making and cognitive control.…”
Section: Discussionmentioning
confidence: 94%
“…Decision scientists have grown increasingly interested in how we control our decisionmaking 1,21,22 . Building off of research into adaptive control mechanisms in other forms of cognitive tasks [23][24][25] , studies have shown that such decision parameters can be shaped by variables such as temporal urgency 4 and choice conflict 2,11,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our results support the TRA in the field of tourism by showing that some cognitive perceptions affect attitudes and behaviours, and even more, by showing how some of these responses vary from country to country. This line follows the most recent complementary approach: how cognitive control research has informed the understanding of decision-making (Frömer and Shenhav, 2022).…”
Section: Discussionmentioning
confidence: 99%